2011
DOI: 10.1111/j.1751-0813.2011.00854.x
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastography in healthy, sick non‐septic and septic neonatal foals

Abstract: Objectives To evaluate citrated recalcified thromboelastography (TEG) in healthy newborn foals, and to determine intra-assay, interindividual and intra-individual (at 12 h, 24 h and 7 days after birth) variations. Additionally, to compare TEG variables, haematological values and conventional coagulation profiles from healthy, sick non-septic, and septic foals.Design Prospective study. MethodsThe study group comprised 18 healthy, 15 sick nonseptic and 17 septic foals. Two citrated (3.2%; 1 : 9 anticoagulant : b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Patients with any of the clinical signs, fever or unexplained leukocytosis (neutrophilia) or elevated acute phase proteins should have their catheterized vein evaluated immediately by clinical examination and ultrasound. (Dunkel et al, 2010;Mendez-Angulo et al, 2011). Virchow described the three factors leading to thrombus formation (Virchow's triad).…”
Section: Clinical Signs and Diagnosis Of Thrombophlebitismentioning
confidence: 99%
“…Patients with any of the clinical signs, fever or unexplained leukocytosis (neutrophilia) or elevated acute phase proteins should have their catheterized vein evaluated immediately by clinical examination and ultrasound. (Dunkel et al, 2010;Mendez-Angulo et al, 2011). Virchow described the three factors leading to thrombus formation (Virchow's triad).…”
Section: Clinical Signs and Diagnosis Of Thrombophlebitismentioning
confidence: 99%
“…Few studies dealt with modification of clotting profile in healthy newborn foals [6,10,14], whereas, to our knowledge, no research on platelet functional activity in equine species are reported during the early postpartum period.…”
Section: Introductionmentioning
confidence: 81%
“…In addition, this study was conducted in healthy horses. Age and the presence of disease will also affect TEG and Sonoclot variables and might be difficult to differentiate from the effects of LMWH . However, serial measurements of the variables measuring change from baseline might overcome these deficiencies.…”
Section: Discussionmentioning
confidence: 97%